A Diverse Contributing Body: A Study of Second Language Writing’s Influence on Writing Studies in Inkshed - Wright-Taylor, Christin (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2024)
In 1961, the CCCC released a report titled “The Freshman Whose Native Language is Not English.” In this report, the chair argued for separate courses dedicated to teaching language-diverse students and staffed by “a linguistic expert, or experts, so that the student may be prepared for and oriented to some of the vagaries of the English language before the Freshman English teacher meets him” (Matsuda, 1999, p. 711). Paul Kei Matsuda (1999) argues that this moment marks the institutional divide between U.S. composition and applied linguistics that would go on to create a vacuum of knowledgeable peers. This vacuum meant that new composition theories interested in language topics in writing were not held accountable by peers trained in applied linguistics. If Matsuda’s assessment of this division of labour in the U.S. is correct, it inspires the question: does the samedivision of labour exist in a Canadian context? How have these two fields related historically, andwhat implications does this relationship (or lack thereof) have on the future of writing instruction inCanada’s increasingly language-diverse classrooms? The purpose of this paper is to construct ahistory of the relationship between these two fields as it pertains to one of Canada’s primary writingorganizations: the Canadian Association for Studies in Language and Learning, also known as Inkshed.This paper first defines the Canadian term for composition, building on Wetherbee Phelps’ (2014) Canadian term “discourse and writing” to create “discourse and writing studies” (DW studies). Next, this paper excavates the Inkshed newsletters and conference programs from 1980 onward for evidence of cross-pollination between DW studies and second language (L2) writing. To further explore the relationship between these two areas in Inkshed’s past, this research builds on the work of Miriam E. Horne who composes a rich picture of Inkshed’s development in her book, Writing in a Community of Practice: Composing Membership in Inkshed.The findings from this paper reveal that during the tenure of Inkshed, DW studies and L2 Writing scholarship comingled and remained closely linked through the decades until the organization dispersed. In other words, in the life of Inkshed, there does not appear to have been the same institutional division of labour between DW studies and L2 Writing as there was between composition and applied linguistics in the US.Ultimately, these findings contribute to the broader narrative of how discourse and writing has professionalized in a Canadian context. They also contribute to the ongoing conversation regarding how writing instructors, writing program administrators, and writing centre professionals can best support culturally and linguistically diverse writers in Canadian classrooms. By drawing on this longstanding relationship with L2 Writing, DW studies scholars and practitioners are uniquely situated to greet the future of higher education equipped with language-based writing theories that are rooted in a community of knowledgeable L2 Writing peers.